Structural Insights Into m6A-Erasers: A Step Toward Understanding Molecule Specificity and Potential Antiviral Targeting - Bayoumi, Mahmoud; Munir, Muhammad (Frontiers in Cell and Developmental Biology, 2021)
The cellular RNA can acquire a variety of chemical modifications during the cell cycle and compelling evidences highlight the importance of these modifications in determining the metabolism of RNA and subsequently cell physiology. Among myriads of modifications, methylation at N6-position of adenosine (m6A) is the most important and abundant internal modification in the mRNA. The m6A marks are installed by methyltransferase complex proteins (writers) in majority of eukaryotes and are dynamically reversed by demethylases such as FTO and ALKBH5 (erasers). The incorporated m6A marks on the RNA transcripts are recognized by m6A-binding proteins collectively called as readers. Recent epigenetic studies have unequivocally highlighted the association of m6A demethylases with a range of biomedical aspects including human diseases, cancers and metabolic disorders. Moreover, the mechanisms of demethylation by m6A erasers represent a new frontier in the future basic research on RNA biology. In this review, we focused on recent advances describing various physiological, pathological, and viral regulatory roles of m6A erasers. Additionally, we aim to analyze structural insights into well-known m6A-demethylases in assessing their substrate binding-specificity, efficiency, and selectivity. Knowledge on cellular and viral RNA metabolism will shed light on m6A-specific recognition by demethylases and will provide foundations for the future development of efficacious therapeutic agents to various cancerous conditions and open new avenues for the development of antivirals.